E-038 CTA Protocol Optimization for Improved Stent Visualization. (26th July 2014) - Durst, C; Starke, R; Norton, P; Hagspiel, K; Gingras, J; Hixson, H; Liu, K; Crowley, R; Gaughen, J; Jensen, M; Evans, A
Abstract : Introduction/purpose: Evaluation of stents using noninvasive imaging can be difficult. Artefact from the metallic struts often limits visibility within the stent on computed tomography angiograms (CTA). Special techniques developed for visualization of cardiac stents using CTA can be adapted for cervical and intracranial stent evaluation. Materials and methods: All studies were performed on a 64 slice GE Discovery 750HD CT scanner (GE Healthcare, Little Chalfont, Buckinghamshire, United Kingdom). The standard arterial phase imaging protocol is performed with 100 mL of contrast administered at a rate of 5 ml/sec. Scan acquisition is triggered when contrast arrives in the aortic arch. Scan coverage extends from the carina to the vertex of the head. Slice thickness is 0.625. Pitch is 1.375:1. Rotation time is 0.5 sec. Tube voltage is 120 kv with a dynamic tube current ranging from 200–350 mA. The raw images are then reconstructed through the stent using a bone plus algorithm at 0.625 mm x 0.3 mm and a field of view of 20 mm. Three fellowship trained neuroradiologists compared the standard CTA sequences with those optimised for visualization of the stent. For each stent, the reader described the patency of the stent (patent, occluded, or mild/moderate/severe stenosis) and their confidence level in their interpretation (high, moderate, or low confidence). Each reader then subjectively determined if they felt the stent CTA was beneficial. Results: The optimised stent protocol uses a harder reconstruction algorithm, small field of view, and thin cuts to optimise the view of content within the stent. All readers agreed that the stent CTA was useful and improved their confidence in stents that were less than 2.5 mm in diameter. Stenosis was routinely overestimated in stents less than 2.5 mm using the standard protocol. In the representative case, the patient presented with stroke like symptoms attributable to the vascular distribution of the stent. On the original CTA (Figure 1a ), the stent was believed to be occluded. However, after reconstructing the image using the stent protocol, the stent was found to be widely patent (Figure 1b ). Conclusions: With the use of a 64 slice CT scanner and a protocol adopted from the cardiac literature, it may be possible to adequately assess the patency of cervical and intracranial stents using CTA. Disclosures: C. Durst: None. R. Starke: None. P. Norton: None. K. Hagspiel: None. J. Gingras: None. H. Hixson: None. K. Liu: None. R. Crowley: None. J. Gaughen: 2; C; Stryker, Covidien, Microvention. M. Jensen: 2; C; Covidien. A. Evans: 2; C; Covidien, Stryker.